Drone-robôs para manutenção de componentes em linhas de transmissão - Souza, Frederico Costa (2023)
The application of robots in high voltage power line maintenance operations has gradually advanced over the last few decades, with emphasis on the segment of mobile robots and drones. However, even with the advances achieved, many problems related to the development of these robots still persist. Among the desirable characteristics for these robots are: reliability; operating autonomy; low weight; high capacity for overcoming obstacles and shielding against electromagnetic interference, many of which until then were little contemplated in existing robots. That said, it was proposed in this thesis the development of drone-robots for maintenance of high voltage power lines. These drone-robots consist of sets formed by a drone that works coupled to different robotic modules, each one of these developed to perform a specific maintenance task. This thesis describes the design, development, construction, and experimental testing of three drone-robots: one for cleaning insulator chains, one for removing debris from the lines, and another for installing stockbridge vibration dampers. This thesis also includes the implementation of attitude control for a drone suitable for transporting the mentioned modules and a procedure for the drone-robots shielding against electromagnetic interference and electrostatic discharges from transmission lines of up to 138 kV. The use of drone-robots in field tests conducted at a power company's facilities demonstrated the efficiency of these robots in overcoming a significant portion of existing limitations, making the developed robots stand out as promising solutions in the high-voltage power line maintenance robot segment.